ISLAMIC EDUCATION STUDENTS’ PERSPECTIVE ABOUT ENGLISH SUBJECT - sulaiman sulaiman sulaiman (Journal of Research and Thought on Islamic Education, 2019)
This research aims to know the perspective of Islamic students about English subject. It reveals the questions such as: 1) what is the perspective of Islamic studies students towards English Subject in State Islamic Institute Pontianak?, 2) how does English learning process help Islamic studies students in State Islamic Institute Pontianak enrich their field study knowledge?. The research used mixed method. To answers the first research question, survey was used as research method, and questioner was used as instrument. Meanwhile, to answer the second research question, qualitative approach was chosen as method to gain answer. Interview was used as data collecting technique. The finding found that Islamic education students had positive perception dealing with the importance of learning English. The result also showed that English learning process on most of students’ perspective had not been effective and it did not give much contribution in increasing students’ English ability which deals with their disciplines. In conclusion, positive perception of students about the importance of learning English was not facilitated enough by learning process. Keywords: Students’ Perspective, Islamic Education Students, English Subject.